Mimesis as conditio humana (Itinera, 2024)
The concept of mimesis originates in the Greek context in the 5th century BC, and since then, it has been at the heart of Western aesthetic reflection. It finds its best-known formulation in the Aristotelian affirmation that “art imitates nature”; however, as C. Wulf has emphasised, the mimetic faculty plays a role not only in the art domain but also in almost all areas of human action, representation, speech and thought:mimesisis aconditio humana. Thus, alongside the passive-imitative meaning of mimesis, we can also identify an active meaning of the term since it indicates a process that leads us to encounter external reality aesthetically and to reproduce its traits creatively, even in our bodies. The topicality of the question lies in this complexity, which connects mimesis not only to the terms of imitation but also to those of individual plasticity and autopoiesis.
Keywords: Mimesis, imitation, autopoiesis, conditio umana.